Sodium-glucose cotransporter 2 inhibitors and fracture risk in patients with type 2 diabetes mellitus: A systematic literature review and Bayesian network meta-analysis of randomized controlled trials. (December 2018) - Azharuddin, Md; Adil, Mohammad; Ghosh, Pinaki; Sharma, Manju
Highlights: NMA reported no association between fracture risk and SGLT2 inhibitors use in T2DM. Subgroup analysis found no association between SGLT2 inhibitors and fracture risk. No inconsistency found between direct and indirect treatment comparison. Abstract: Aim: To perform a systematic literature review and network meta-analysis (NMA) of randomized controlled trials (RCTs) to estimate effect of SGLT2 inhibitors on fracture risk in patients with T2DM. Methods: A systematic search was performed on PubMed/Medline and ClinicalTrials.gov from inception to May 2018 to identify RCTs reporting fracture events with the use of SGLT2 inhibitors compared to control group in patients with T2DM. NMA within a Bayesian framework was performed to calculate the odds ratio (OR) and 95% credible intervals (CrI) using random effect model. Node splitting method was applied to evaluate the presence of inconsistency for NMA. Results: A total of 40 RCTs including 32, 343 T2DM patients with 466 fracture cases. Pairwise meta-analysis showed no association between risk of fracture and SGLT2 inhibitors use (OR = 1.01, 95%CI 0.83–1.23; p = 0.91; I 2 = 27%) compared with the control group. The NMA has shown a non-significant association with fracture risk and canagliflozin (OR = 0.57, 95%CrI 0.12–1.90), dapagliflozin (OR = 0.58, 95%CrI 0.13–2.00), and empagliflozin (OR = 0.78, 95%CrI 0.23–2.80) use when compared to placebo. No association was also found among SGLT-2 inhibitors (canagliflozin OR = 2.6, 95%CrI 0.69–16.00; dapagliflozin OR = 2.6, 95%CrI 0.52–22.00; and empagliflozin OR = 3.7, 95% CrI 1.0–27.00), when compared to active treatment. Node-splitting analysis shows non-significant inconsistency between direct and indirect comparisons. Conclusion: The current NMA result suggests no detrimental effect of SGLT2 inhibitors on fracture risk in patients with T2DM. Further RCTs and real-world studies with long-term follow up are required to confirm the present findings.